Prolonged Systemic Inflammation Alters Muscarinic Long-Term Potentiation (mLTP) in the Hippocampus. (15th January 2021) - Shavit-Stein, Efrat; Dori, Amir; Shimon, Marina Ben; Gofrit, Shany Guly; Maggio, Nicola
Abstract : The cholinergic system plays a fundamental role in learning and memory. Pharmacological activation of the muscarinic receptor M1R potentiates NMDA receptor activity and induces short-term potentiation at the synapses called muscarinic LTP, mLTP. Dysfunction of cholinergic transmission has been detected in the settings of cognitive impairment and dementia. Systemic inflammation as well as neuroinflammation has been shown to profoundly alter synaptic transmission and LTP. Indeed, intervention which is aimed at reducing neuroinflammatory changes in the brain has been associated with an improvement in cognitive functions. While cognitive impairment caused either by cholinergic dysfunction and/or by systemic inflammation suggests a possible connection between the two, so far whether systemic inflammation affects mLTP has not been extensively studied. In the present work, we explored whether an acute versus persistent systemic inflammation induced by LPS injections would differently affect the ability of hippocampal synapses to undergo mLTP. Interestingly, while a short exposure to LPS resulted in a transient deficit in mLTP expression, a longer exposure persistently impaired mLTP. We believe that these findings may be involved in cognitive dysfunctions following sepsis and possibly neuroinflammatory processes.